Cruise report for the April 2009 Gulf of Alaska Line-Transect survey (GOALS) in the Navy training exercise area - Rone, Brenda K.; Douglas, Annie B.; Clapham, Phillip; Martinez, Anthony; Morse, Laura J.; Calambokidis, John (Monterey, California. Naval Postgraduate School, 2009)
The United States Navy, which maintains a maritime training area in the central Gulf of Alaska (GoA), funded a vessel-based line-transect survey during April 2009 to determine marine mammal species distribution and abundance in the training area. The survey cruise employed multiple observation techniques, including visual and passive acoustic observations, as well as photographic identifications. Results of the survey are presented in this document. During the survey cruise, fin whales were the most common large cetacean visually sighted, while sperm whales were the most common large cetacean acoustically detected. Not unexpectedly, because the cruise did not have any sonobuoys, no baleen whales were detected acoustically. However, photographic identifications of fin and killer whales were quite successful, with 23 individuals (4 fin and 19 killer whales) preliminarily identified from the 721 photographs collected.